EFEKTIFITAS IMPLEMENTASI MANAJEMEN PENINGKATAN MUTU BERBASIS SEKOLAH DI SD - Heny Puspita (UNIVERSITAS BENGKULU, 2015)
The objective of this research is to describe implementation of School based quality management in public elementary school number 1 Selupu Rejang, Rejang Lebong regency. Themethod of the research is qualitative descriptive, which try to describe to research phenomenon based on the condition. Subject of the research is principal, teacher, officer, student, and schoolcommite. The data collecting through interview, observation, and documentation. Then qualitative data is used to support and complete qualitative data. The result of the research is thatimplementation of school number 1 Selupu Rejang, Rejang Lebong regency is not done well.Keywords: implementation, school based quality management.